Dimensi Keteraturan Sosial Wanita Hamil dalam Gamitan Superstisi Kubuang Tigo Baleh - Ridha Hasnul Ulya (Kafa`ah: Journal of Gender Studies, 2018)
This research aims to describe the form, meaning and dimension of pregnant women’s social order from the perspective of superstition. This research is a qualitative research as the technique of data collection was done through observation and unstructured interview. The data analysis was done through three steps; data reduction, data display and conclusion. Based on the data analysis it can be concluded that: (1) superstition belong pregnant women in Kubuang Tigo Baleh is the form of communication, (2) superstition of pregnant women in Kubuang Tigo Baleh is assocative, (3) superstition of pregnant women in Kubuang Tigo Baleh is always formed through event context. In other words, superstition of pregnant women in Kubuang Tigo Baleh aims to make pregnant women always careful in doing their manners. The carefullness in behaving is the effort to create social order